SISTEM PENGENDALIAN LAMPU BERBASIS ARDUINO MENGGUNAKAN BLUETOOTH PADA SMARTPHONE ANDROID DI RUMAH QUR’AN AL-FATAH - moh muthohir; Laksamana Rajendra Haidar; Husamuddin Islami (Elkom : Jurnal Elektronika dan Komputer, 2018)
The purpose of this research is to produce tangible results in providing comfort or convenience in turning on or off the night life at home everyday, especially for people who forget to turn off the lights. The method used in making microcontroller-based home lighting control using an android smartphone is. This research method consists of several stages, analysis methods, design methods, implementation testing methods, and maintenance. The results achieved are improving the aspects of comfort and convenience for agencies, where this series of tools works after bluetooth devices are available on android smartphones. connected to a bluetooth module which is connected to the Arduino microcontroller. Basically, the principle of using this tool is that users must be able to operate a smartphone based on the Android operating system. The conclusion of this research is that the Arduino-based light control device using bluetooth can fulfill its function to control the lights properly and the device is designed to be minimalist and safety so it is safe to use.